Pengembangan Modul Tematik Kelas IV Berbasis Kearifan Lokal Papua Barat Daya - Suci Nurul Santi; Anis Alfian Fitriani; Asrul Asrul (STKIP Andi Matappa Pangkep, 2023)
Teaching materials that can support thematic learning as well as facilitate students with local-scale materials need to be developed because the teaching materials in the form of thematic books published by the Ministry of Education and Culture used do not yet integrate the local wisdom of Southwest Papua. One of the teaching materials that can be developed is a module. This study aims to describe the level of validity of developing thematic modules for class IV, the sub-theme of the uniqueness of the area where I live based on the local wisdom of Southwest Papua. This research is a Research and Development (R&D) study using a 4D model which is modified into 3D with the stages of define, design and develop. The results of this study indicate that based on validity test data, thematic modules meet the very valid category with an assessment percentage of 88.8%. Based on these results, it can be concluded that the class IV thematic module, the sub-theme of the uniqueness of the area where I live based on the local wisdom of Southwest Papua, is stated to be very valid to use in the learning process.